1982
DOI: 10.1176/ajp.139.6.741
|View full text |Cite
|
Sign up to set email alerts
|

Aggression, suicide, and serotonin: relationships to CSF amine metabolites

Abstract: In an earlier, separate study, the authors found that human aggression and suicide (a specific aggression-related behavior) were associated with lower levels of CSF 5-hydroxyindoleacetic acid (5-HIAA), a serotonin metabolite. That study focused on subjects with personality disorders without affective illness. In the present study they examine the life history of aggression and history of suicidal behavior in 12 subjects with borderline personality disorders without major affective disorder. Histories of aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 689 publications
(44 citation statements)
references
References 52 publications
1
41
1
1
Order By: Relevance
“…Altogether the data yield a different interpretation than postulated in earlier studies with rodents, primates and humans (Brown et al, 1982; Grimes et al, 2006; Howell et al, 2007). The use of DHT plus aromatase inhibition in our model enabled disassociation of TPH2 mRNA expression, and perhaps serotonin production, from axonal serotonin content.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Altogether the data yield a different interpretation than postulated in earlier studies with rodents, primates and humans (Brown et al, 1982; Grimes et al, 2006; Howell et al, 2007). The use of DHT plus aromatase inhibition in our model enabled disassociation of TPH2 mRNA expression, and perhaps serotonin production, from axonal serotonin content.…”
Section: Discussioncontrasting
confidence: 72%
“…The actions of androgens on aggression were linked to low serotonin for many years (Bonson et al , 1994; Brown et al , 1982; Coccaro et al , 1997; Higley et al , 1996; McGinnis, 2004; Stanley et al , 2000). Indeed, studies of different compartments of the serotonin system indicated that anabolic steroids decreased serotonin in terminal fields throughout the hamster brain (Grimes and Melloni, 2006); and elevated aggression correlated with low concentrations of the serotonin metabolite, 5HIAA, in male macaque cerebral spinal fluid (CSF) (Howell et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since it is assumed that the intensity dependence of auditory evoked potentials is inversely related to serotonergic tone, our data seems to suggest an early decrease in serotonergic tone in stroke patients with AB. This is in line with previous studies which demonstrated reduced CSF concentration of 5-HIAA in individuals with history of aggression [9,10] and impulsive aggression [11]. …”
Section: Discussionsupporting
confidence: 93%
“…Concentration levels of both serotonin (5-HT) and its main metabolite, 5-hydoxyindoleacetic acid (5-HIAA) were originally described to be lower in aggressive respect to nonaggressive subjects [8]; moreover, reduced CSF concentration of 5-HIAA was demonstrated in individuals with a history of aggression [9,10] and impulsive aggression [11]. …”
Section: Introductionmentioning
confidence: 99%
“…A clinical characteristic of patients with impulsive aggression has been associated with evidence of diminished central serotonergic function in studies of cerebrospinal fluid (CSF) monoamine metabolites. Diminished levels of CSF 5-HIAA are reported in borderline personality disorder patients with violent behavior or impulsive aggression (Brown et al, 1982; Linnoila et al, 1983; Traskman-Bendz, Asberg & Schalling, 1986; Virkkunen, Nuutila, Goodwin & Linnoila, 1987). Pharmacologic challenge studies with serotonergic agonists such as d,l-fenfluramine or ipsapirone have shown a close relationship between aggression and serotonin (Fallon, Keator, Mbogori, Turner & Potkin, 2004; Minzenberg et al, 2006; Siever et al, 1999).…”
Section: Resultsmentioning
confidence: 99%